ANALISIS EFEKTIVITAS PROGRAM TENAGA KERJA MANDIRI (TKM) DI KABUPATEN PURWAKARTA (Studi Kasus : Desa Taringgullandeuh Kecamatan Kiarapedes) - Nurfauziah, Nisa Maulida; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2020)
Tenaga Kerja Mandiri (TKM) program is a program to empower unemployed citizens by giving them entrepreneurship preparation, business fund, and regular assistance done by guidance staff. The method used in this paper is a descriptive qualitative method by using interviews, observation, and documentation to collect the data. The indicators to measure the effectiveness of this program are object accuracy, program socialization, goal completion, and educative monitor and control systems. The research result using those four factors shows the implementation of the Tenaga Kerja Mandiri (TKM) program has not been fully effective yet since there are still some obstacles during the process. Several factors support the effectiveness of this program, such as the high interest of Taringgullandeuh residents and also the excellent performance of the trainers. However, several factors also hamper the effectiveness of this program, such as the location of the village that is quite distant from the town center and the conservative residents, limited funding and infrastructure, lack of participation from the government in promoting the products, and the ineffectiveness role of the guidance staff. Therefore, the researcher offers several suggestions for the implementation of this program, such as the government need to be wiser in selecting the target of this program, be more active in promoting this program through various media, and promoting the products produced by the fostered community regularly. The government also needs to give a clear penalty to the guidance staff who do not provide effective assistance.